2013
DOI: 10.1021/am4029894
|View full text |Cite
|
Sign up to set email alerts
|

Controlled and Triggered Small Molecule Release from a Confined Polymer Film

Abstract: A device composed of a poly (N-isopropylacrylamide)-co-acrylic acid (pNIPAm-co-AAc) microgel layer sandwiched between two thin Au layers (all on a glass support) was used as a novel platform for controlled and triggered small molecule delivery. Tris (4-(dimethylamino)phenyl)methylium chloride (Crystal Violet, CV), which is positively charged, was loaded into the microgel layer of the device and released in a pH dependent fashion, at a rate that could be controlled by the thickness of the Au layer coating the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 59 publications
3
62
1
Order By: Relevance
“…Thus, DOX-HCl loaded on superparamagnetic nanoparticles coated with chitosan and employing a folate ligand-activated trigger can improve the system of drug delivery to the cancer cells. The results obtained in this study are in good agreement with the values given in the literature [23].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, DOX-HCl loaded on superparamagnetic nanoparticles coated with chitosan and employing a folate ligand-activated trigger can improve the system of drug delivery to the cancer cells. The results obtained in this study are in good agreement with the values given in the literature [23].…”
Section: Discussionsupporting
confidence: 92%
“…The saturation magnetization of ZnFe 2 O 4 nanoparticles is higher when synthesized at higher temperatures [18,25]. Hence, the results obtained in this study are in good agreement with the literature [23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These networks also undergo a swollen-to-collapsed transition in water at elevated temperature. 24 In previous work, we showed that optical devices, known as etalons, could be generated by "sandwiching" a homogeneous monolayer of pNIPAm-co-AAc microgels between two thin Au layers. [21][22][23] Like all temperature induced conformational state changes of pNIPAm, the transition for pNIPAm-based microgels is fully reversible over many cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Specically, pNIPAm-based microgels transition from a swollen (large diameter) to a collapsed (small diameter) state at elevated temperature. 4,[23][24][25][26][27][28][29][30][31][32] The structure of this device can be seen in Fig. PNIPAmbased microgels can also be made responsive to other stimuli, in addition to temperature.…”
Section: Introductionmentioning
confidence: 99%